Asymmetric Synthesis of α-Chloro-α-halo Ketones by Decarboxylative Chlorination of α-Halo-β-ketocarboxylic Acids - Kitahara, Kazumasa; Mizutani, Haruna; Iwasa, Seiji; Shibatomi, Kazutaka (Synthesis, 2019)
Chiral α-chloro-α-fluoro ketones were synthesized by enantioselective decarboxylative chlorination of α-chloro-β-ketocarboxylic acids in the presence of a chiral amine catalyst. The reaction yielded the corresponding α-chloro-α-fluoro ketones with moderate-to-high enantioselectivity (up to 90% ee). The method was also applied to the synthesis of α-bromo-α-chloro ketones with 90% ee.
Keywords: decarboxylative chlorination; chiral amine catalyst; enantioselective synthesis; β-ketocarboxylic acids; fluorinated compounds